Pembelajaran Fikih Ibadah Anak Usia Dini: Studi Model Pembelajaran Shalat di Raudhatul Athfal - Machani Machani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to examine and describe the prayer learning model applied in Raudhatul Athfal (RA) Baitul Qur'an. The approach used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The researcher acts as the main instrument assisted by supporting tools in the form of interview guidelines, mobile phones, and field notes. The data obtained are analyzed through the stages of data reduction, grouping data into certain units, categorization, checking the validity of the data (including credibility, transferability, dependability, and confirmability), as well as interpretation and drawing conclusions. The results of the study indicate that the prayer learning model in RA Baitul Qur'an includes classical, group, corner, area, cooperative, and direct learning models. The programs implemented include: (a) introduction to ablution members, ablution procedures, and prayers before and after prayer; (b) introduction to prayer movements and memorization of prayers in and after prayer; and (c) practice of prayer implementation, namely the practice of praying every Friday and dhuha prayer every two weeks. These models are used to instill an understanding and skills of prayer worship in early childhood in a gradual and enjoyable way.